Analisis Pelaksanaan Sertifikasi Iso 9001 : 2008 Puskesmas Kalasan Kabupaten Sleman - Khamidah Yuliati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
The background of the study was the implementation of standardization of health service quality stated in ISO 9001: 2008 in Kalasan Health Center effectively applied on July 9th, 2009. It was hoped that the implementation of standardization of basic health service quality increase the quality of health service and human resources. The data collection was conducted by interview and questionnaire, and the collected data were in the form of primary and secondary data. The number of the research sample was 40 respondents. The data analysis method used was descriptive. The result of the research includes: (1) Based on the result of descriptive analysis in the implementation of ISO 9001: 2008 certification, the implementation of employee duty needs job knowledge and skill so that they can work as their responsibility. (2) The sub-variable of Employee Work Satisfaction was included in employee involvement in all lines so that the goal of the health center was achieved. (3) The sub-variable of employee work environment means having cooperation with other employees in all lines. (4) The sub-variable of Kalasan Health Center was obtained from work practice experience, in all service departments that focus on the increase of the service quality in Kalasan Health Center appropriately. The conclusions of the research result and analysis were (1) all employees increase the service quality for all patients in Kalasan Health Center. The curative aspect was emphasized on outpatients, and the stabilization of emergency and referral patients. (2) Acknowledging qualified work achievements by giving the opportunity to have position promotion as procedure assigned. Work satisfaction was from the existing of formation facility or space condition that gave comfort feeling. (3) Work team and colleague feeling needed to be maintained so that priority gap got decreased. The coordination between the employer and the employee is useful to finish the work. (4) The institution gave guarantee on health service quality which was as the hope of the consumer (patient) and strengthened the competitiveness. Therefore, the implementation of quality management system based on the concept of ISO 9001:2008 as the effort to strengthen the competitiveness was urgent.